2014
DOI: 10.1007/s10336-014-1058-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prevalence and intensity of infection with malaria parasites in the Blue Tit

Abstract: Parasite species are usually specialists utilising specific host species, but parasite assemblages may differ substantially even between populations of the same species and show seasonal and annual fluctuations. Host characteristics such as individual age and sex may also affect parasite species composition and abundance. Here, we report the occurrence of malaria parasites in the Blue Tit (Cyanistes caeruleus) inhabiting Gotland (Sweden) across 5 years. Using PCR-based techniques, we found eight cytochrome b l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
22
2
Order By: Relevance
“…This suggests that the effect of infection might be masked in a combined analysis. In contrast to the above studies, in which the majority of infections was caused by parasites from one genus: either Plasmodium or Haemoproteus, in our population the majority of infections is caused by two parasite species, from both genera: P. circumflexum and H. majoris (Podmokła et al 2014b). Because both of them are expected to negatively affect host survival prospects, we predict lower survival rates of infected individuals compared to uninfected ones and potentially different effects of infections with Plasmodium and Haemoproteus.…”
contrasting
confidence: 98%
See 2 more Smart Citations
“…This suggests that the effect of infection might be masked in a combined analysis. In contrast to the above studies, in which the majority of infections was caused by parasites from one genus: either Plasmodium or Haemoproteus, in our population the majority of infections is caused by two parasite species, from both genera: P. circumflexum and H. majoris (Podmokła et al 2014b). Because both of them are expected to negatively affect host survival prospects, we predict lower survival rates of infected individuals compared to uninfected ones and potentially different effects of infections with Plasmodium and Haemoproteus.…”
contrasting
confidence: 98%
“…We investigated the potential effect of avian malaria infections, as well as individual age and sex, on the survival prospects in the blue tit. Our study population is exposed to infection with parasites from the Plasmodium and Haemoproteus genera, with the former genus being the dominant one (Podmokła et al ). Previous studies on blue tits in populations infected with only one parasite genus or sporadically also with the other genus have shown a negative effect of Haemoproteus parasites on host survival (Martinez‐de la Puente et al 2010) and a small effect of Plasmodium on survival (Lachish et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensity of infection (parasite DNA copy number) was then quantified via qPCR, comparing a focal sample with standard curves created using full-length cyt b PCR products from P. circumflexum and H. majoris (as described in (Knowles et al 2011). (For more details on primers, reaction setups, reagent concentrations and instruments, please see Podmokła et al (2014a, b)).…”
Section: Methodsmentioning
confidence: 99%
“…Cosgrove et al (2008) found that increase in vector abundance was followed by an increase in Plasmodium prevalence from spring to autumn within a blue tit Cyanistes caeruleus population, but prevalence was also positively correlated with the age of the host individuals. Others found changes in infection status within individual hosts even within the reproductive season (Knowles et al 2011) and also between years (Knowles et al 2011;Lachish et al 2011;Podmokla et al 2014). However, none of them tried to investigate the possible factors behind and the fitness consequences of changes in individual infection status.…”
Section: Introductionmentioning
confidence: 99%